Unburned spheroidal attapulgite building rubbish ceramic grain - GU JIAJUN; XU QINGHUA; XU SHENGYING; JIN BAIYUN (2012)
The invention discloses an unburned spheroidal attapulgite building rubbish ceramic grain. According to the technical scheme, the unburned spheroidal attapulgite building rubbish ceramic grain is composed of high-viscosity attapulgite clay powder, attapulgite clay tailing powder, building rubbish powder, red bentonite powder, kieselguhr tailing powder and cement. The raw materials of the unburnedspheroidal attapulgite building rubbish ceramic grain are mixed, pelletized, maintained and screened, and then are packed as the unburned spheroidal attapulgite building rubbish ceramic grain. The unburned spheroidal attapulgite building rubbish ceramic grain is spheroidal in shape, has a rough and hard surface, is provided with fine pores inside and is the building ceramic grain with light weight, high strength, excellent chemical stability, durability and excellent heat-insulating and sound-insulating effect. The building rubbish and tailings are comprehensively utilized to produce the unburned spheroidal attapulgit